2013
DOI: 10.1086/670213
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Hawthorne Effect: Reduction of Clostridium difficile Environmental Contamination through Active Intervention to Improve Cleaning Practices

Abstract: Education and passive observation resulted in a significant improvement in housekeeper disinfection of nontoxigenic Clostridium difficile spores artificially inoculated onto surfaces in C. difficile infection rooms. A further significant reduction occurred with direct supervision and real-time feedback, suggesting that optimal disinfection is achieved by working closely with housekeepers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 9 publications
1
20
0
2
Order By: Relevance
“…For instance, patients who were aware of being in a study had less post-operative knee pain than subjects who were unaware [25]. Being aware of ongoing monitoring was associated with improvement in decontamination hospital practices [26].…”
Section: Discussionmentioning
confidence: 97%
“…For instance, patients who were aware of being in a study had less post-operative knee pain than subjects who were unaware [25]. Being aware of ongoing monitoring was associated with improvement in decontamination hospital practices [26].…”
Section: Discussionmentioning
confidence: 97%
“…Several other studies have demonstrated different results after instituting direct observation, supervision, and education of staff as they clean, again often showing reductions of important hospital pathogens (257,(261)(262)(263)(264). There is a concern that these interventions might lose impact over time, since cleaning is physically demanding, poorly paid, and subject to inadequate staffing (17,265).…”
Section: Observation Supervision and Education Of Housekeeping Staffmentioning
confidence: 99%
“…Checklists to instruct housekeepers on the cleaning sequence should be promoted 13. Moreover, education, implementation of standardized processes, and direct interaction with or to domestic staff are all interventions that have been reported to improve the efficiency of disinfection of contaminated surfaces.32,56 New automated technologies, such as hydrogen peroxide, have been reported to be effective against C. difficile spores. 33,[57][58][59] This approach can only be used in vacant rooms, needs special equipment and personnel, has a relatively high cost, and is associated withsignificant turnaround time.…”
mentioning
confidence: 99%